New Insights into Theriogenology - Payan-Carreira, Rita (Veterinary Medicine and Science, 2018)
This book covers a variety of topics on animal reproduction and reproductive medicine. With evolving technology and a continual increase in knowledge, regarding domestic pets or agricultural animals, new information is available on diverse topics in this broad field. The book contents reflect the individual experience of authors, who developed a number of themes identified as attracting interest in the field. As it is, new opportunities were opened for productive collaboration. We have tried to provide you with current, specialised information that may be useful to students, clinicians and researchers. We hope this book inspires you to embrace these themes, foster the debate on particular topics and may be used as a start-up source for exploring the theriogenology field.